Knowledge-based Language Teaching and its Implications on Teacher Education: Perceptions of Teacher Educators in Pakistan - Haji Karim Khan; Muhammad Naeem Butt (The Journal of Humanities & Social Sciences, 2021)
Research on the language teachers’ knowledge has always remained a grey area in Pakistan. Urdu and English are generally the medium of instruction in schools, whereas English is the sole medium of instruction in the mainstream universities. Both Urdu and English are being taught as languages in schools, too. Besides Urdu and English, respective provincial languages are also in practice in schools. The question, what knowledge should our language teachers know, and what are their implications for teacher education, have always received lesser attention in the country. Through the use of a qualitative case study approach, we explored perceptions of teacher educators regarding language teachers’ knowledge. Data were collected through in-depth interviews from nine teacher educators from Departments/Institutes of Education of two public sector universities in Khyber Pakhtunkhwa and one university as well as one Elementary College of Education in Skardu, Pakistan. A thematic analysis was employed for data analysis. Findings showed that besides content, pedagogy, and pedagogical content knowledge, language teachers need to know cultural knowledge and knowledge of using IT resources and research findings in their routine practices. As a result, some key implications for language teacher development have surfaced from the findings.